Let c and b be the roots of x2-6x-2=0 (cb). If

an=cn-bn where (n=1)

then a10-2a8/2a9 =

  1. 1
  2. 2
  3. 3
  4. 4

c and b are the roots of the equation : x2-6x-2=0 (c>b)............(1)
if an=cn-bn (n1)
c is the root of eq(1): therefore 
c2-6c-2=0c2=6c+2.........(2)
multiplying through out by  cn-2 on the both sides:
cn=6cn-1+2cn-2.........(3)
similarly bn=6bn-1+2bn-2..........(4)
subtracting eq(4) by eq(3):
cn-bn=6(cn-1-bn-1)+2(cn-2-bn-2)an=6an-1+2an-2........(5)
now put n = 10
a10=6a9+2a8
therefore a10-2a8=6a9
hence
a10-2a82a9=6a92a9=3
hope this helps you

  • 124
What are you looking for?